SISTEM INFORMASI MONITORING VISIBILITY MATERIAL PROMO (MATPRO) OUTLET DI PT INDOSAT, TBK SALES AREA JAMBI BERBASIS WEB: MATERIAL PROMO: OUTLET: WEBSITE: MYSQL - Pariyadi; Darma Putra, Soferli (FORTECH (Journal of Information Technology), 2019)
Promotion through the installation of Material Promos (MATPRO) is an effective marketing strategy. Because it can show how to communicate with potential customers to motivate them to understand and respond to what is in the programming with the goal of increasing sales. PT Indosat, Tbk Sales Area Jambi is a leading telecommunications company. In this case, promotion is needed so that the public can find out what products are currently available, especially in outlets. The process of monitoring visibility of MATPRO in outlets at PT Indosat, Tbk by the Marketing Communications division still uses Ms. Excel so the report cannot show real time to management. Besides that, human error factors can also occur because they have not been properly systemized. So, to solve the problem we make an Information System of Monitoring Promo Material (MATPRO) visibility in outlets PT Indosat, Tbk Sales Area Jambi Web based. This Information system can show the real time report and minimizes the human error. So that it can help PT Indosat, Tbk in monitoring the visibility of MATPRO in outlets effectively and efficiently.